Implementasi Program BSPS dalam Penyediaan Rumah Layak Huni di Desa Balai Kasih Kecamatan Kuala Langkat - Maswandhani Destriando; Victor Lumbanraja (Yayasan Literasi Sains Indonesia, 2024)
Implementation is an inseparable part of policy implementation, because without implementation a program cannot be implemented. The Self-Help Housing Stimulant Assistance Program is a program designed for Low-Income Communities to have a house that is livable and carried out independently. This research aims to provide an overview and explanation of how the Self-Help Housing Stimulant Assistance Program is implemented in providing livable houses in Desa Balai Kasih Kecamatan Kuala Kabupaten Langkat. This research uses qualitative research methods using a descriptive approach. The results of the research show that the Program Implementor has worked optimally, but there are several shortcomings. This is due to the fact that socialization has not been evenly carried out among the people of Desa Balai Kasih, which has led to people's ignorance about this program. Apart from that, there is no definite schedule of activities, which means that people who receive aid do not know when their houses will be worked on and when they will be completed. Based on I nterviews with the community, the implementation of the Self-Help Housing Stimulant Assistance Program in Desa Balai Kasih is helping the people of Desa Balai Kasih to have houses that are suitable for living in.